A systematic study on the effect of co-catalysts composition on the performance of Ziegler-Natta catalyst in ethylene/1-butene co-polymerizations. (18th November 2022) - Masoori, Maryam; Nekoomanesh, Mehdi; Posada-Pérez, Sergio; Rashedi, Reza; Bahri-Laleh, Naeimeh
Abstract: Effect of the type and composition of conventional co-catalysts on the catalytic performance of Ziegler-Natta catalysts has been investigated by means of a combined experimental and theoretical study. Two fully alkylated co-catalysts (triethylaluminium, TEA, and triisobuthylaluminium, TIBA) and their combinations with two chlorinated ones, DEAC (diethylaluminiumchloride) and EADC (ethylaluminiumdichloride), were employed in ethylene/1-butene co-polymerization using a commercial TiCl4 /MgCl2 catalyst. The highest co-polymerization rate was found for TEA and TIBA, without the addition of chlorinated co-catalysts. According to the high temperature gel permeation chromatography and the rheometric mechanical spectrometer analyses, the composition of DEAC with TEA and TIBA lead to the production of polymers with the highest molar mass and longer relaxation times. The promising influence of chlorinated Al-alkyl co-catalysts was on the comonomer incorporation since the combination of TIBA + DEAC could promote it up to 34%. Eventually, to elucidate the role of the co-catalysts on the comonomer response, density functional calculations were performed using ethylene and propylene as monomers. Lower energy barrier was observed in propylene insertions in the presence of DEAC and TIBA co-catalysts, demonstrating their positive impact on comonomer response, in comparison to TEA and EADC, which confirm the experimental evidence. Graphical abstract: Image 1 Highlights: Effect of cocatalysts composition on catalyst performance was unraveled in ethylene/butene copolymerization via ZN process. DEAC containing system exhibited improved comonomer response with homogenous distribution. In DFT simulations, a lower energy barrier was observed for comonomer insertions using DEAC as co-catalyst. The overall findings clearly highlight the positive effect of combined co-catalysts to enhance the comonomer response.